Textual Criteria in Ghazi Al-Gosaibi's Poem Hadiqat Al-Ghoroob/ المعايير النَّصية في قصيدة حديقةُ الغروبِ لغازي القصيبي - Norah Abdulrahman Alabdulali (Ijaz Arabi Journal of Arabic Learning, 2026)
The importance of the research lies in its idea, as it specializes in a poem from modern Saudi literature by the poet Ghazi Al-Gosaibi. The research aims to study the textual standards in the poem (Hadigat Al-Ghoroob), and to clarify its elements . The research is based on the descriptive textual method that is based on analyzing the poetic verses according to the linguistic textual standards, and clarifying their components. The researcher reached a set of results, the most important of which are: References varied between the situational and the textual, and the situational was abundant due to the connection of the idea of the poem to the poet. The poem contained repetition, deletion, connection, and intertextuality.It achieved acceptability, intentionality, informational, and situational . The sender was Al-Qusaibi and the receiver was the public in general and his daughter Hadeel in particular.The time was Al-Qusaibi's last days and the place was Saudi Arabia.The channel was writing. The system was classical Arabic. The form of the message was poetry. The key was his supplication and trust in the Lord of the Worlds in his suffering, his plea to the Lord of the Worlds for relief and acceptance and his declaration for forgiveness. The text was harmonious and interconnected in meaning.